2016
DOI: 10.1016/j.pharep.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan oligosaccharides promote diabetic wound healing by increasing angiogenesis

Abstract: This suggests that topical application of O-HA could be a useful method by which to treat diabetic wounds in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 20 publications
0
44
0
1
Order By: Relevance
“…These oligosaccharides are able to interact with two critical EC receptors: CD44, playing a major role in EC adhesion and proliferation, and RHAMM (Receptor for HA-Mediated Motility), essential for EC invasion [202,203,204]. The role of LMW-HA in affecting angiogenesis during wound healing, diabetic mellitus and endometriosis, suggests the possibility to modulate HA as a putative therapeutic approach [205,206]. In contrast, high molecular weight HA (HMW-HA) was reported to be anti-angiogenic [207,208] and immunosuppressive [209].…”
Section: Hyaluronan: Not Only a Mere Gluementioning
confidence: 99%
“…These oligosaccharides are able to interact with two critical EC receptors: CD44, playing a major role in EC adhesion and proliferation, and RHAMM (Receptor for HA-Mediated Motility), essential for EC invasion [202,203,204]. The role of LMW-HA in affecting angiogenesis during wound healing, diabetic mellitus and endometriosis, suggests the possibility to modulate HA as a putative therapeutic approach [205,206]. In contrast, high molecular weight HA (HMW-HA) was reported to be anti-angiogenic [207,208] and immunosuppressive [209].…”
Section: Hyaluronan: Not Only a Mere Gluementioning
confidence: 99%
“…Therefore, a large amount of research is currently focused on vascular regeneration to promote wound healing by enhancing angiogenesis. Many studies have reported that increasing wound angiogenesis can signi cantly promote wound repair [17][18][19][20][21]. However, because wound repair is a pathophysiological process involving multiple factors, any unbalanced factors will cause abnormal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK/ERK signaling pathway plays an important role in cell proliferation, metabolism and apoptosis [ 29 ]. Initiation of Src/ERK signaling by TGF-β is important for the promotion of vascularization in the wound site [ 30 ]. SSCS showed significant effects on the expressions levels of TGF-β and CD31 in wounded tissues, especially in the early stages of wound healing, and had remarkable effects on the healing of seawater-immersed wounds, its promotional effect was superior to that of chitosan and gauze.…”
Section: Discussionmentioning
confidence: 99%